ANALYSIS OF CHANGES IN THE FOREIGN LANGUAGE LEXICON USED BY THE MILLENNIAL GENERATION IN THE X APPLICATION IN INDONESIA - Moh Fikri Taufiqul Haq; Adityawan Hendratno; Mohammad Nawfal Arfa; Abdullah Faqih Amanullah; Endang Sholihatin (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
The language lexicon that has changed in the X application is more widely used by the millennial generation. The users of the X application, who are mostly from the millennial generation, now tend to use this variety of language not only in socializing through the application, but also in their daily lives. For example, the word "Open Minded" is used to express something that must be accepted with an open mind, the word "Red Flag" is used to give someone indirect or direct rejection, and so on. Apart from that, this research aims to find out: 1) The variety of foreign languages ​​used by the millennial generation on the "X" application in Indonesia and 2) To find out changes in the foreign language lexicon used by the millennial generation on the "X" application in Indonesia. This research uses qualitative methods with data sources in the form of posts or tweets in the "X" application, with data collection techniques through observation, documentation (screenshots) of tweets in the "X" application. Based on this research, it can be concluded that: 1) The variety of languages ​​used by the Indonesian millennial generation on the "X" application is influenced by foreign languages ​​and 2) Changes in the foreign language lexicon of the millennial generation on the "X" application in Indonesia include a reinterpretation of the word "Open Minded" which is often interpreted negatively, and indicates judgment towards people who are deemed to lack understanding. While "Red Flag" is used to express a bad assessment of social behavior, especially in the context of relationships.